Observations on Experimental Two-boat Bottom and Midwater Trawling in Gandhisagar Reservoir - K.N., Kartha; K.S., Rao (Fishery Technology, 2025)
Among the two trawl designs employed for two-boat bottom trawling 12.50m dual purpose trawl caught 33.22% more fish than 12.50m large mesh high opening trawl. The increase in the average catch/h of fish is 60.53% in dual purpose trawl due to attachment of false head rope. The influence of trawling speed of 2-4knots, on the species wise catch composition of fish obtained during experimental two-boat bottom and midwater trawling is discussed.